A pilot study of pars plana vitrectomy, intraocular gas, and radial neurotomy in ischaemic central retinal vein occlusion. Issue 9 (20th August 2003) - Williamson, T H; Poon, W; Whitefield, L; Strothoudis, N; Jaycock, P
Abstract : Background/aims: There is no effective treatment for ischaemic central retinal vein occlusion (CRVO). The two major negative outcomes are neovascular glaucoma (NVG) and severe central visual loss. In this study pars plana vitrectomy (PPV), mild panretinal photocoagulation, and intraocular gas injection were employed to prevent NVG. The potential role of incision of the lamina cribrosa (radial neurotomy) for visual recovery was examined. Methods: Eight eyes of seven patients with ischaemic CRVO had PPV, mild panretinal photocoagulation, and intraocular perfluoropropane gas injection. Four eyes had radial neurotomies performed. The patients were examined by fundus photography, fundus fluorescein angiography, optical coherence tomography, and Goldmann visual field analysis. Results: No patients suffered from neovascular glaucoma. Visual recovery was seen in patients with and without neurotomy but some patients had cataract extraction to allow visualisation for PPV. Fundus photography demonstrated reduced engorgement of retinal veins in two of the patients with neurotomy and one with PPV alone. Optical coherence tomography demonstrated macular oedema in three patients with neurotomy and all patients with PPV alone. Segmental visual field loss was seen in one patient with neurotomy suggesting damage to the optic nerve head. Conclusions: PPV is safe in ischaemic CRVO. Combined with mild PRP and intraocular gas injection the risk of neovascular glaucoma is low. Neurotomy can be added to try to improve the chances of recovery of central vision but may cause additional peripheral visual field loss.